Traduction du futur antérieur de probabilité en polonais. Problème d'héritage sémantique dans la description des parties du corps - Grigowicz, Anna (Neophilologica, 2007)
The article deals with the problem of semantic heredity in the semantic class of the parts of the body. This is an analysis situated within the frame of the object-oriented perspective propagated by W. Banyś, used to describe 89 words belonging to the above-mentioned category. Problems with ascribing particular parts of the body to the proper superclasses were described, as well as the criteria used to distinguish the main three superclasses all the elements belonging to the object class of the parts of the body can be qualified to.